Synergistic effect of Zn doping on thermoelectric properties to realize a high figure-of-merit and conversion efficiency in Bi2−xZnxTe3 based thermoelectric generators. Issue 20 (6th May 2022) - Kumar, Rishikesh; Bhatt, Ranu; Tewary, Arpan; Debnath, A. K.; Bhatt, Pramod; Mani, Navaneethan; Jha, Purushottam; Patro, Pankaj; Bhattacharya, Shovit; Pathak, Manbendra; Khan, M. K.; Singh, Ajay; et al.
Abstract : The synergistic effect of decoupled thermoelectric parameters on the enhanced power output of a unicouple TEG. Abstract : In state-of-the-art bismuth telluride based thermoelectric devices, the n-type composition shows a lower figure-of-merit ( zT ) than the p-type counterpart due to intrinsic electrical anisotropy and bipolar conduction at elevated temperatures. Herein, we demonstrate a significant improvement in the zT values of n-type Bi2− x Zn x Te3 ( x = 0–0.3) materials through aliovalent Zn doping at the Bi-site in the rhombohedral Bi2 Te3 structure. A simultaneous enhancement in the electrical conductivity ( σ ) and Seebeck coefficient ( α ) with Zn doping is observed, which is attributed to the increased carrier concentration ( n ) and effective mass ( m *), respectively. Concomitantly, a drastic enhancement in the power factor ( α 2 σ ) from 2.4 mW m −1 K −2 ( x = 0) to 3.1 mW m −1 K −2 ( x = 0.2) at 430 K is achieved. In addition, the incorporation of Zn shows a significant reduction in the lattice and bipolar contributions to the total thermal conductivity ( κ ), which drastically enhances the zT value to ∼1.2 ( x = 0.2) at 450 K. The achieved zT value is ∼70% higher than that of the undoped Bi2 Te3 sample. A unicouple module fabricated using n-type Bi1.8 Zn0.2 Te3 in combination with the compatible high zT p-type Bi0.5 Sb1.495 Cu0.005 Te3 material shows a record-high conversion efficiency ( η ) of ∼8.1% at a temperature gradient (Δ T ) of 224 K. The achieved η is amongst the best-reported values till date in Bi2 Te3 lab-scale thermoelectric power generators.